Fatal Autonomic Dysfunction Due to Guillain-Barre Syndrome After Cardiac Surgery - SELÇUK, EMRE; SELÇUK, Emre; KÖKSAL, CENGİZ; KÖKSAL, CENGİZ (My University, 2022)
Guillain-Barre syndrome, a rare peripheral neuropathy, appears to occur more often in patients who have recently undergone surgery than in the general population. However, the pathophysiologic relationship between surgery and Guillain-Barre syndrome is elusive. Few cases of Guillain-Barre syndrome after cardiac surgery have been reported. Autonomic dysfunction, a serious complication of Guillain-Barre syndrome, has not been previously reported after cardiac surgery.
Keywords: Autonomic nervous system diseases/complications/physiopathology; axons/pathology; Guillain Barré syndrome / complications / diagnosis / etiology / physiopathology / therapy; fatal outcome; immunoglobulins, intravenous; therapeutic use; muscle weakness; etiology; plasmapheresis; postoperative complications